2015
DOI: 10.1016/j.yjmcc.2015.06.016
|View full text |Cite
|
Sign up to set email alerts
|

Decreased creatine kinase is linked to diastolic dysfunction in rats with right heart failure induced by pulmonary artery hypertension

Abstract: Our objective was to investigate the role of creatine kinase in the contractile dysfunction of right ventricular failure caused by pulmonary artery hypertension. Pulmonary artery hypertension and right ventricular failure were induced in rats by monocrotaline and compared to saline-injected control animals. In vivo right ventricular diastolic pressure–volume relationships were measured in anesthetized animals; diastolic force–length relationships in single enzymatically dissociated myocytes and myocardial crea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
52
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 45 publications
2
52
0
1
Order By: Relevance
“…We interpreted this as a decreased ability of MCT myocytes to respond to an increase in demand, which is a definition of heart failure. We concluded that decreased CK expression leads to diastolic dysfunction, via local reduction in ATP:ADP ratio and thus to Ca 2+ ‐independent force production and diastolic sarcomere shortening …”
Section: Pulmonary Artery Hypertension and Diastolic Dysfunctionmentioning
confidence: 92%
See 4 more Smart Citations
“…We interpreted this as a decreased ability of MCT myocytes to respond to an increase in demand, which is a definition of heart failure. We concluded that decreased CK expression leads to diastolic dysfunction, via local reduction in ATP:ADP ratio and thus to Ca 2+ ‐independent force production and diastolic sarcomere shortening …”
Section: Pulmonary Artery Hypertension and Diastolic Dysfunctionmentioning
confidence: 92%
“…The end diastolic pressure–volume relationship (EDPVR) was measured using a Millar catheter inserted into the RV of anesthetized animals. The EDPVR was significantly steeper in monocrotaline‐injected rats (MCT; [FAIL in Fowler et al …”
Section: Pulmonary Artery Hypertension and Diastolic Dysfunctionmentioning
confidence: 99%
See 3 more Smart Citations